Pengaruh Penilaian Guru Terhadap Hasil Belajar Siswa - Ahsan Zhouri; Rahmat Irfandi (LPPM Politeknik Pratama, 2023)
Low student learning outcomes are influenced by assessments and evaluations that are not carried out by the teacher in the learning process. This is because the teacher's understanding of this assessment or evaluation is only to give questions to students. So an assessment must be carried out from the beginning of learning so that learning is achieved. the goal. And this has a positive and significant influence on student assessment of overall student learning outcomes, there is a positive and significant influence between student learning independence on overall student learning outcomes, and there is a positive and significant influence between learning motivation and student learning independence on student learning outcomes together.